2013
DOI: 10.1002/bit.24999
|View full text |Cite
|
Sign up to set email alerts
|

Quality by design approach for viral clearance by protein a chromatography

Abstract: Protein A chromatography is widely used as a capture step in monoclonal antibody (mAb) purification processes. Antibodies and Fc fusion proteins can be efficiently purified from the majority of other complex components in harvested cell culture fluid (HCCF). Protein A chromatography is also capable of removing modest levels of viruses and is often validated for viral clearance. Historical data mining of Genentech and FDA/CDER databases systematically evaluated the removal of model viruses by Protein A chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 26 publications
6
34
0
Order By: Relevance
“…Protein A chromatography, in contrast, is not expected to bind significant amounts of virus since it is an affinity resin. Virus partitioning studies show that significant levels of virus are found in the protein A flowthrough and wash fraction as expected, however virus is also detected in the elution pool (Brorson et al, ; Lute et al, ; Zhang et al, ).…”
mentioning
confidence: 69%
“…Protein A chromatography, in contrast, is not expected to bind significant amounts of virus since it is an affinity resin. Virus partitioning studies show that significant levels of virus are found in the protein A flowthrough and wash fraction as expected, however virus is also detected in the elution pool (Brorson et al, ; Lute et al, ; Zhang et al, ).…”
mentioning
confidence: 69%
“…For certain feedstocks tested, LRVs were lower without a clear correlation with any processrelated factors, including equilibration and wash buffers, resin, and elution conditions. For a given mAb, LRVs were generally consistent, and insensitive to process parameter changes including load density (g mAb/L resin), flow rate, temperature, intermediate wash buffer composition, pH, conductivity, and pooling within the ranges tested (M. Zhang et al, 2014). For a given mAb, LRVs were generally consistent, and insensitive to process parameter changes including load density (g mAb/L resin), flow rate, temperature, intermediate wash buffer composition, pH, conductivity, and pooling within the ranges tested (M. Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 82%
“…These results indicate that the non-mAb HCCF components in mAbs 1, 2, and 3 were not the main cause of low LRVs, but appeared to contribute to impact the final HCCF LRVs based on the fact that the HCCF LRVs were higher than those with the pure mAbs, especially in the cases of mAbs 1 and 2 ( Figure 1). Zhang et al, 2014). Moreover, it was the mAb itself, not the other HCCF impurities in the feed, that caused reduced LRV.…”
Section: Batch Protein a Chromatographymentioning
confidence: 99%
See 2 more Smart Citations